DAMPAK PEMODERASIAN KOMPONEN ARUS KAS TERHADAP HUBUNGAN LABA AKUNTANSI DENGAN RETURN SAHAM - ARI DHARMA LAKSMI, PUTU; DWI RATNADI, NI MADE (Jurnal Ilmiah Akuntansi dan Bisnis, 2009)
Accurate information regarding listed companies is crucial tominimize investment risk. This research aims to examine the effect ofaccounting income on stock return, and the effect of cash flow fromoperation, cash flow from investment, and cash flow from financingactivities respectively as moderating variables on the relationshipbetween accounting income and stock return of manufacturer listedon the Jakarta Stock Exchange.There were 161 manufacturing companies listed during 2001to 2005, and 39 of them are selected as sample research usingpurposive sampling method. With 5 year research period, there are195 observations done. Data then are analyzed using multiple linearregressions.Results show that accounting income affect stock returnsignificantly, which is shown by greater value of t count compare to ttable. While cash flow from operation, investment, and financingactivities are not able to moderate relationship between accountingincome and stock return.
Keywords: moderating variables, cash flow, accounting income, stock return.